PENGGUNAAN ALAT PERMAINAN EDUKATIF DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI RAUDHATUL ATHFAL AL-HIDAYAH GUNUNG TERANG LABUHAN RATU LAMPUNG TIMUR - Arif Andriyani; Eca Gesang Mentari (Institut Agama Islam Negeri Metro, 2021)
Early childhood is a very appropriate period to introduce an educational game tool, this age is very sensitive to environmental stimuli, children have a high curiosity. Cognitive abilities develop when children play, children can grow their attention and focus. Children are always active, enthusiastic and curious. Therefore, the research that has been carried out by researchers has a research focus, namely the use of educational game tools in developing cognitive abilities of early childhood in RA AL-Hidayah Gunung Terang Labuhan Ratu, East Lampung. The research questions in this study are: 1) How is the use of educational game tools in developing cognitive abilities of early childhood in RA AL-Hidayah Gunung Terang Labuhan Ratu, East Lampung?, 2) What are the supporting and inhibiting factors of educational game tools in RA AL-Hidayah Mount Bright Labuhan Ratu, East Lampung?. The objectives of this study are: 1) To determine the extent to which the use of educational game tools in developing early childhood cognitive abilities at RA AL-Hidayah Gunung Terang, 2) To determine the supporting and inhibiting factors of the use of educational game tools in developing cognitive abilities of young children. early at RA AL-Hidayah Gunung Terang Labuhan Ratu, East Lampung. This type of research is a qualitative descriptive field, which takes place in RA AL-Hidayah Gunung Terang Labuhan Ratu, East Lampung. The data sources used are primary data and secondary data sources. The data collection method used in this research is to use the method of observation, interviews, and documentation. Based on the results of research and analysis, it can be concluded that the use of educational game tools in developing cognitive abilities of early childhood in RA AL-Hidayah Gunung Terang Labuha Ratu, East Lampung has been realized well. The results of the teacher's achievement in developing cognitive abilities of early childhood group B at RA AL-Hidayah Gunung Terang Labuhan Ratu, East Lampung are the ability to recognize numbers, say numbers 1-20, count simple numbers, arrange number puzzles and sort numbers, recognize shapes and colors.